Waste less time on Facebook — follow Brilliant.
×

Need Your Help!

A motor boat, moving upstream passess a drifting raft. 1 hour later, the boat's motor breaks. it takes 45 min to fix it. while the boat is drifting downstream. after that, the boat begins to chase the raft and passes it. \(S=11 \text{ km}\) away from the place where they met first. What is the current \(v\) of the river.

Note by Nosa Wahyu
1 year, 9 months ago

No vote yet
1 vote

  Easy Math Editor

MarkdownAppears as
*italics* or _italics_ italics
**bold** or __bold__ bold

- bulleted
- list

  • bulleted
  • list

1. numbered
2. list

  1. numbered
  2. list
Note: you must add a full line of space before and after lists for them to show up correctly
paragraph 1

paragraph 2

paragraph 1

paragraph 2

[example link](https://brilliant.org)example link
> This is a quote
This is a quote
    # I indented these lines
    # 4 spaces, and now they show
    # up as a code block.

    print "hello world"
# I indented these lines
# 4 spaces, and now they show
# up as a code block.

print "hello world"
MathAppears as
Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.
2 \times 3 \( 2 \times 3 \)
2^{34} \( 2^{34} \)
a_{i-1} \( a_{i-1} \)
\frac{2}{3} \( \frac{2}{3} \)
\sqrt{2} \( \sqrt{2} \)
\sum_{i=1}^3 \( \sum_{i=1}^3 \)
\sin \theta \( \sin \theta \)
\boxed{123} \( \boxed{123} \)

Comments

Sort by:

Top Newest

We have that the raft travels 11 km. Lets call his traveled distance \( S_1 = v_r * t_1= 11 km \). His speed is \( v_1= v \) of the river ( \(v_r\) ), so \( v_1 = v_r \). The distance that the boat travels for that 1 hour after it meets the raft is \( S_2 = v_2 * t_2\) . \(t_2 = 1\) and \(v_2 = v_b - v_r\) {\(v_b\) is the speed of the boat} . \(S_2 = v_b - v_r\) . \(S_3\) is the distance traveled during the engine was broken. \(v_3 = v_r\) and \(t_3 = 3/4\) h. \(S_3 = 3/4 * v_r\) . \(S_4\) is the distance from when he fixes the engine to where he passes the raft. \(v_4 = v_b + v_r\). We have \(t_4\) and \(S_4 = v_4 * t_4 . t_1 = t_2 + t_3 + t_4\) ; \(t_1 = 7/4 + t_4\) ; \(t_4 = t_1 - 7/4\)

\(S_1+ S_2 = S_3 + S_4\) \(11 + v_b - v_r = 3/4 * v_r + (v_b + v_r) * t_4\) \(v_r * (7/4 + t_4) - v_m * (1 - t_4) = 11\) \(v_r * t_1 - v_m * (1 - t_4) = 11\) \(11 - v_m * (1 - t_4) = 11\) \(v_m * (1 - t_4) = 0\) /(v_m = 0) or \(1- t_4 = 0\) \(v_m\) is bigger than zero because it is speed so \(1 - t_4 = 0\); \(t_4 = 1\) \(t_1 = 7/4 + t_4 = 11/4\); \(S_1 = t_1 * v_r\); \(v_r = 4 km/h\)

Jack Nikolov - 1 year, 9 months ago

Log in to reply

×

Problem Loading...

Note Loading...

Set Loading...